2019
DOI: 10.3390/diagnostics9040192
|View full text |Cite
|
Sign up to set email alerts
|

Novel Data Mining Methodology for Healthcare Applied to a New Model to Diagnose Metabolic Syndrome without a Blood Test

Abstract: Metabolic Syndrome (MetS) is a cluster of risk factors that increase the likelihood of heart disease and diabetes mellitus. It is crucial to get diagnosed with time to take preventive measures, especially for patients in locations without proper access to laboratories and medical consultations. This work presented a new methodology to diagnose diseases using data mining that documents all the phases thoroughly for further improvement of the resulting models. We used the methodology to create a new model to dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In the diagnosis of Type II DM, it was shown that a possible diagnosis can be made without the physician based on the physiological findings of the patient [25]. In a study about diagnosing metabolic syndrome without blood tests, the rate of making the correct diagnosis was determined as 85.12% [45]. The analysis of adipocytokines and anthropometric levels obtained from obese women (diabetic and non-diabetic) with experimental data set and the probability of having DM in women with obesity was tried to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In the diagnosis of Type II DM, it was shown that a possible diagnosis can be made without the physician based on the physiological findings of the patient [25]. In a study about diagnosing metabolic syndrome without blood tests, the rate of making the correct diagnosis was determined as 85.12% [45]. The analysis of adipocytokines and anthropometric levels obtained from obese women (diabetic and non-diabetic) with experimental data set and the probability of having DM in women with obesity was tried to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…However, connected AI doctors could make their own independent decisions, considering the other AI doctors’ opinions. For example, a single patient living in a small village in Siberia or Tibet could benefit from comparing diagnosis coming from a thousand AI doctors [ 116 , 117 , 118 ]. AI could provide more accurate, faster, and cheaper health care for everyone.…”
Section: Challenges and Prospectsmentioning
confidence: 99%